THE CREATION OF HICHAT : SECURE MOBILE CHAT USING HYBRID CRYPTOSYSTEM - Handayani, Linda (Universitas Gunadarma, 2024)
Security of chat transmission or exchange is very important in the application of communication. Secret messages are sent or exchanged through communication services in cyberspace where no other party should have authority other than the sender and recipient to protect against harm. This causes the need for a cryptographic system that is used to maintain security during the transmission or exchange of chats. Hybrid cryptosystem is a technique that combines symmetric and asymmetric encryption to create a safer and more efficient system. This study proposes the creation of a secure mobile-based chat application, namely Hichat, by combining the AES algorithm to encrypt chat and the RSA algorithm to create keys. The hash function is also used to authenticate API keys to server services. The purpose of this study is to create a secure mobile-based chat application that prioritizes confidentiality, integrity, authentication and non-repudiation. The functional testing carried out obtained results that all features were running well. Security testing was carried out using a sniffing technique attack which showed that the message information and API keys were encrypted and the scenario results showed that every aspect of security was successful. Then the application display is responsive on several devices.